Focal Point: Third Swiss COST Chemistry Symposium - Alan F. Williams (CHIMIA, 2003)
Over a hundred scientists attended the third Swiss COST Chemistry workshop in Basel last October 2002. The scientific programme consisted of some sixty posters illustrating Swiss participation in COST programmes, and ten invited lectures which progressed from small molecule synthesis, via catalysis and diagnostics to chemistry in biological systems.